Penerapan Prinsip Kelangsungan Usaha Dalam Perkara Kepailitan PT Njonja Meneer - Mochamad Cholil (Jurnal Hukum Lex Generalis, 2025)
This research is motivated by the bankruptcy case of PT Njonja Meneer, a traditional herbal company with historical and economic value. The study focuses on the application of the going concern principle in Indonesian bankruptcy law. The findings show that in this case, the principle of business continuity was not fully considered, as the court prioritized debt repayment through asset liquidation. The conclusion is that the application of the going concern principle in PT Njonja Meneer’s bankruptcy was not optimal, leading to implications for business sustainability and labor protection.